Peningkatan Kapasitas Usaha Pada PKM Usaha Olahan Pisang di Kabupaten Bombana - Gusti R. Sadimantara; Sitti Leomo (Jurnal SIAR ILMUWAN TANI, 2020)
Bananas are tropical fruit commodities that are very popular and have a high potential to be managed intensively and agribusiness oriented. Banana plants have many benefits for human needs so that they have high economic value. Bananas can play a role as food substitutes containing calories, protein, carbohydrates, fats, vitamins, and minerals that are needed by the human body. The potential development of bananas is quite significant because it has broad adaptability to various agro-climate zones and has excellent potential for commercial growth as an export commodity. The market potential abroad is enormous and continues to increase. The domestic market's potential also increased due to rising levels of income and quality of life. There are many obstacles to increasing domestic banana production. Besides, processed banana products have not optimally produced as a source of livelihood and community income. This PKM partner business group has prospective business potential to be developed, because the banana and processed banana-based market is enormous, both at local and national levels. The banana production business that has developed has not been economically productive due to various limitations and constraints on land availability. In such conditions, bananas have cultivated as inserted plants. However, these two farmer groups have the potential to be productive farmer groups. The introduction of shade-tolerant bananas can be a solution for increasing banana production on limited land through the intercropping system. While the introduction of improvements to the processing and packaging system of Dempok bananas can improve the added value and quality of the products produced